2014
DOI: 10.3168/jds.2013-7250
|View full text |Cite
|
Sign up to set email alerts
|

Goat milk consumption modulates liver divalent metal transporter 1 (DMT1) expression and serum hepcidin during Fe repletion in Fe-deficiency anemia

Abstract: Iron deficiency is the most prevalent micronutrient deficiency worldwide. In spite of the crucial role of hepatocyte divalent metal transporter 1 (DMT1) and hepcidin in Fe metabolism, to date, no studies have directly tested the role of these proteins in liver Fe metabolism during Fe repletion after induced Fe-deficiency anemia. Therefore, the aim of the current study was to assess the effect of goat or cow milk-based diets on Fe metabolism in one of the main body storage organs, the liver, during the course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
2
9
0
1
Order By: Relevance
“…Multiple factors regulate the expression of hepcidin in the liver. As expected, low serum hepcidin levels were recorded in the PEP due to the increased expression of key duodenal proteins involved in iron absorption [20], favoring red blood cell production during insufficient dietary iron supply. On the other hand, inflammation is a strong inducer of hepcidin production and release from the liver [21][22][23], resulting in reduced iron release from stores and macrophages, thereby reducing iron in the circulation and disrupting iron homeostasis [24].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Multiple factors regulate the expression of hepcidin in the liver. As expected, low serum hepcidin levels were recorded in the PEP due to the increased expression of key duodenal proteins involved in iron absorption [20], favoring red blood cell production during insufficient dietary iron supply. On the other hand, inflammation is a strong inducer of hepcidin production and release from the liver [21][22][23], resulting in reduced iron release from stores and macrophages, thereby reducing iron in the circulation and disrupting iron homeostasis [24].…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, the increased liver DMT1 protein levels faithfully reflect the increased liver iron storage after dietary iron repletion [18] and, this way, the increase in DMT1 protein expression in anemic animals fed fermented goat milk reveals that iron repletion is more efficient, a finding that is supported and corroborated by the higher iron storage in the rats fed fermented goat milk compared with fermented cow milk. As previously reported, goat milk fat is richer in medium-chain triglycerides, which are oxidized in the mitochondria, providing fast energy discharge used in several metabolic pathways [19] and thus contributing to increasing the synthesis of carrier proteins such as DMT1 [20]. On the other hand, goat milk has more than twice the vitamin A content of cow milk [19], and this vitamin increases liver DMT1 protein expression by posttranscriptional regulation via increased protein translation or decreased degradation [18].…”
Section: Discussionmentioning
confidence: 86%
“…Besides Ca, dairy products contain a range of nutrients including proteins (whey and casein), branched-chain amino acids, and peptides. In this sense, goat milk and dairy contain a somewhat lower amount of caseins, and so its proportion of serum proteins is higher, explaining the greater digestive utilization made of goat milk protein than of cow milk protein. , Murphy et al also showed an inverse relationship between dairy protein and all adiposity measures, with control for total dietary protein. These data support previous research, which has indicated that dairy protein might be the component responsible for beneficial effects on body composition …”
Section: Discussionmentioning
confidence: 99%
“…At the end of the EP, all of the hematological parameters were recovered with both fermented milk-based diets; however, serum Fe was lower in the anemic group fed fermented cow milk compared with its controls, revealing that Fe repletion was more efficient with fermented goat milk. This fact can be explained due to the beneficial nutritional characteristics and bioactive components of goat milk and dairy, which favor Fe absorption and potentiate the liver DMT1 Fe-transport activity and expression, enhancing Fe metabolism and storage compared with cow milk …”
Section: Discussionmentioning
confidence: 99%
“…Composición corporal de las ratas alimentadas durante 30 días con dietas basadas en leche fermentada de vaca o cabra Los productos lácteos contienen una amplia gama de nutrientes que incluyen proteínas (suero y caseína), aminoácidos de cadena ramificada, y péptidos. En este sentido, la leche de cabra y sus derivados lácteos contienen una cantidad algo menor de caseínas y una mayor proporción de proteínas séricas, lo que explica la mejor utilización digestiva de la proteína de la leche de cabra con respecto a la de vaca (20,21). .…”
Section: Discussionunclassified